Relationship between Anthropometric indices, serum Leptin and Respiratory function in Myanmar male adult subjects (Asian Journal of Medical Sciences, 2019)
Background: The role of leptin in respiratory function has been studied in specific respiratory disease. A little is known about the association of serum leptin level and respiratory function parameter in healthy subjects.Aims and Objectives: This study aimed to investigate the relationship between anthropometric indices, serum leptin and respiratory function in Myanmar male adult subjectsMaterial and Methods: A community- based cross-sectional comparative study was carried out in 101 apparently healthy male adult subjects of age 18-45 years. All participants were categorized by anthropometric indices into non- obese (body mass index: BMI < 25 Kg/m2 and obese subjects (BMI > 30 Kg/m2). Differences in respiratory function parameter and serum leptin level were compared across the group. Spirobank II spirometer was used to measure respiratory function (FEV1, FVC, FEV1/FVC, PEFR and FEF25-75%). Serum leptin level was investigated by enzyme-linked immunosorbent assay.Results: The percentage of predicted value of all respiratory function parameters of obese group was significantly lower than that of non-obese group (p